Recent Perspectives in Pyrolysis Research - Bartoli, Mattia; Giorcelli, Mauro (IntechOpen, 2022)
Recent Perspectives in Pyrolysis Research presents and discusses different routes of pyrolytic conversions. It contains exhaustive and comprehensive reports and studies of the use of pyrolysis for energy and materials production and waste management.